CD40 induces an antimicrobial response against the intracellular pathogen Streptococcus agalactiae in Nile tilapia, Oreochromis niloticus. Issue 1 (21st September 2020) - Xia, Hongli; Fan, Huimin; Long, Meng; Cheng, Jun; Chen, Wenjie; Yu, Dapeng; Xia, Liqun; Lu, Yishan
Abstract: Streptococcus agalactiae is a Gram‐positive facultative intracellular bacterium that leads to severe economic loss of tilapia worldwide. Previous studies demonstrated that CD40 contributes to host protection against intracellular injection. In this study, CD40 was characterized from Nile tilapia ( Oreochromis niloticus ), named OnCD40. Sequence analysis showed that open reading frame of OnCD40 was 933 bp, containing a single peptide, a transmembrane domain and four cysteine‐rich domains. The qRT‐PCR revealed that OnCD40 was expressed in all examined tissues with the most abundant ones in spleen and thymus. After S. agalactiae stimulation, the expression of OnCD40 was significantly induced in most of the detected organs. Moreover, OnCD40‐overexpressing fish elicited significant protection against subsequent S. agalactiae challenge; approximately 10000‐fold fewer bacteria were detected in spleen of OnCD40‐overexpressing fish in comparison with control fish. Thus, CD40 had protecting function in Nile tilapia against intracellular pathogens.